Clinical Evaluation of Resin-Based Composites in Posterior Restorations: 12-Month Results - Celik, Cigdem; Arhun, Neslihan; Yamanel, Kivanc (European Journal of Dentistry, 2010)
Objectives: The purpose of this study was to evaluate and compare the 12 month clinical performances of two different posterior composites in Class I and Class II restorations.Methods: Thirty-one patients (10 male, 21 female) were recruited into the study. A total of 82 Class I and Class II cavities were restored with either a nanohybrid composite (Grandio) or a low-shrinkage composite (Quixfil), using their self etch adhesives (Futura Bond and Xeno III) according to manufacturers instructions. The restorations were clinically evaluated 1 week after placement as baseline, and after 6 and 12 months post-operatively using modified USPHS criteria by two previously calibrated operators. Statistical analysis were performed using Pearson Chi-square and Fishers Exact Test (P<.05).Results: All patients attended the 12-month recall. Lack of retention was not observed in any of the restorations. With respect to color match, marginal adaptation, secondary caries and surface texture, no significant differences were found between two restorative materials tested after 12 months (P>.05). None of the restorations had marginal discoloration and anatomic form loss on the 12 month follow-up. Restorations did not exhibit post-operative sensitivity at any evaluation period.Conclusions: Clinical assessment of nanohybrid (Grandio) and low-shrinkage posterior composite (Quixfil) exhibited good clinical results with predominating alpha scores after 12 months. However; further evaluations are necessary for the long-term clinical performance of these materials. (Eur J Dent 2010;4:57-65)
Keywords: Clinical evaluation; Nanohybrid composites; Posterior composites